2014
DOI: 10.1093/schbul/sbu054
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Schizophrenia and Rheumatoid Arthritis: A Nationwide Population-Based Swedish Study on Intraindividual and Familial Risks

Abstract: Numerous studies have reported a reduced risk of rheumatoid arthritis (RA) in schizophrenia. The mechanisms are unknown, but recent genome-wide association studies of schizophrenia have shown strong associations with markers spanning the major histocompatibility complex region, indicating a possible role for adaptive immunity also in schizophrenia. In this population-based cohort study, we assess the associations between RA and schizophrenia and the extent to which any observed associations are specific to RA/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 35 publications
4
48
0
Order By: Relevance
“…Although the prevalence of anxiety disorders is reportedly increased in RA , we could not identify prior studies reporting the incidence of anxiety disorders. Our findings regarding the increased incidence of bipolar disorder in RA are consistent with 1 previous study which evaluated the association of RA and bipolar disorder . In that study of 2,570 individuals with RA from Taiwan and 2,570 individuals without RA, matched on age, sex, comorbidities, and date of enrollment in the national health insurance plan, RA was associated with a 2‐fold increased incidence of bipolar disorder .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although the prevalence of anxiety disorders is reportedly increased in RA , we could not identify prior studies reporting the incidence of anxiety disorders. Our findings regarding the increased incidence of bipolar disorder in RA are consistent with 1 previous study which evaluated the association of RA and bipolar disorder . In that study of 2,570 individuals with RA from Taiwan and 2,570 individuals without RA, matched on age, sex, comorbidities, and date of enrollment in the national health insurance plan, RA was associated with a 2‐fold increased incidence of bipolar disorder .…”
Section: Discussionsupporting
confidence: 91%
“…In that study of 2,570 individuals with RA from Taiwan and 2,570 individuals without RA, matched on age, sex, comorbidities, and date of enrollment in the national health insurance plan, RA was associated with a 2‐fold increased incidence of bipolar disorder . Two other studies failed to showed associations between RA and bipolar disorder . These differences may reflect differences in study design or study populations.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, the 8.1 AH conferring susceptibility to BD also confers susceptibility to an atypical form of rheumatoid arthritis characterized by the absence of the pathognomonic anti‐citrullinated protein antibodies . In this context, it is of interest to note that in SZ, RA is a rare medical comorbidity while in BD it is not uncommon . Hence, we predict that BD‐associated RA may be dominated by the above‐mentioned atypical form.…”
Section: Discussionmentioning
confidence: 94%
“…The earliest interest connecting autoimmunity and schizophrenia stems from a repeated finding of a low prevalence of rheumatoid arthritis in individuals with schizophrenia, beginning with studies in the 1950’s and including analyses up to the present (Eaton et al, 1992; Oken and Schulzer, 1999; Pilkington, 1955; Sellgren et al, 2014; Trevathan and Tatum, 1953; Vinogradov et al, 1991). The finding was replicated more than a dozen times, and various explanations were offered, such as that neuroleptic medications had a protective effect; or that persons with schizophrenia were less likely to report pain; or that life as an inpatient was less physically active and thereby less prone to raising risk for rheumatoid arthritis.…”
Section: Autoimmunity and Schizophreniamentioning
confidence: 99%